2008
DOI: 10.3168/jds.2008-1297
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Differentially Expressed Proteins in Bovine Milk During Experimentally Induced Escherichia coli Mastitis

Abstract: The objectives of the current study were to profile changes in protein composition using 2-dimensional gel electrophoresis on whey samples from a group of 8 cows before and 18 h after infection with Escherichia coli and to identify differentially expressed milk proteins by peptide sequencing using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry post source decay. Only proteins present in whey fractions of all 8 cows were sequenced to avoid reporting a protein response unique to onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
129
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(149 citation statements)
references
References 32 publications
17
129
2
1
Order By: Relevance
“…Clinical mastitis causes decreases in caseins, α-lactalbumin and β-lactoglobulin [10] and increases in serum albumin and serotransferrin. Further studies have identified additional proteins with altered expression in milk from dairy cows with experimental induction of mastitis [11][12][13]. These studies have revealed increased concentrations of chaperonins, DNA-binding proteins, enzymes, transport proteins and structural proteins, complement factors C3 and C4, lactoferrin, transferrin, apolipoprotein AI, fibrinogen, glycosylation-dependent cell adhesion molecule-1, peptidoglycan recognition receptor protein and cyclic dodecapeptide-1.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical mastitis causes decreases in caseins, α-lactalbumin and β-lactoglobulin [10] and increases in serum albumin and serotransferrin. Further studies have identified additional proteins with altered expression in milk from dairy cows with experimental induction of mastitis [11][12][13]. These studies have revealed increased concentrations of chaperonins, DNA-binding proteins, enzymes, transport proteins and structural proteins, complement factors C3 and C4, lactoferrin, transferrin, apolipoprotein AI, fibrinogen, glycosylation-dependent cell adhesion molecule-1, peptidoglycan recognition receptor protein and cyclic dodecapeptide-1.…”
Section: Introductionmentioning
confidence: 99%
“…Further, phosphorylation and glycosylation of bovine κ-CN have also been characterized by Holland et al (2006). However, the published comparative proteomic analyses have mostly focused on host defense proteins in bovine milk that protect the neonate/mammary gland against infection or diagnostic markers of mastitis in affected animals (Boehmer et al, 2008). Few published reports have studied the effects of dietary nutrient supply on expression profile changes in milk protein composition using proteomics.…”
Section: Introductionmentioning
confidence: 99%
“…Milk production is a defining feature of dairy cows. Several factors, such as cow health, environment, lactation stage, genetics and diet, can influence milk protein content and yield (Schingoethe, 1996;Boehmer et al, 2008). In addition, synchronizing the degradation of ruminal carbohydrate and protein by changing diet ingredients can theoretically maximize microbial protein synthesis to support milk production (Casper et al, 1999;Cole and Todd, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Albumin is a plasma protein whose elevation in milk indicates disintegration of the blood-milk barrier (Vangroenweghe et al, 2004). The observed elevation in milk albumin after high-dose post-ruminal infusion of LNA was consistent with changes in the protein composition of milk seen during naturally and experimentally induced mastitis (Hogarth et al, 2004;Boehmer et al, 2008;Boehmer et al, 2010;Ibeagha-Awemu et al, 2010). In the current study, the elevated albumin and SCC in milk were accompanied by disintegration of the blood-milk barrier, suggesting a metabolic stress of mammary gland owing to the LNA infusion.…”
Section: Discussionmentioning
confidence: 52%